Geometric-Phase Metasurfaces Based on Anisotropic Reflection: Generalized Design Rules - Minovich, Alexander E.; Zayats, Anatoly V. (ACS photonics, 2018)
Metasurfaces based on the control of a geometric phase have been proven as one of the most efficient designs for both transmission and reflection operation. However, the constituent nanostructures are often studied only numerically in order to find the best geometric parameters while lacking the analysis of physical principles of their operation and, therefore, predictability. Here we formulate a general concept for the design of reflection-type geometric-phase metasurfaces based on anisotropic reflective nanostructures. We demonstrate that the simplest anisotropic element such as a wire-grid polarizer can be used as a building block of a geometric-phase metasurface with operation bandwidth over the entire visible spectrum. We show that a similar anisotropy-based principle is the basis of a widely used plasmonic resonator design for reflective metasurfaces, and we derive and analyze the conditions for achieving high efficiency and broadband performance for the plasmonic nanoantenna metasurfaces. We demonstrate that the concept of the reflection anisotropy can also be applied to devise reflective metasurfaces built from high-contrast dielectric materials (such as titanium dioxide nanopillars) with a structure height almost 3 times lower compared to the waveguide-mode-based designs. We also show how a broadband metasurface performance in the visible range can be achieved utilizing multiple resonances. The general rules for the reflective metasurface design that we formulate here can provide useful guidelines and hints for the engineering of metasurfaces for practical purposes and applications.